2008
DOI: 10.1007/s00125-008-1008-x
|View full text |Cite
|
Sign up to set email alerts
|

Src activation generates reactive oxygen species and impairs metabolism–secretion coupling in diabetic Goto–Kakizaki and ouabain-treated rat pancreatic islets

Abstract: Aims/hypothesis Na + /K + -ATPase inhibition by ouabain suppresses ATP production by generating reactive oxygen species (ROS) and impairs glucose-induced insulin secretion from pancreatic islets. To clarify the signal-transducing function of Na + /K + -ATPase in decreasing ATP production by the generation of ROS in pancreatic islets, the involvement of Src was examined. In addition, the significance of Src activation in diabetic islets was examined. Methods Isolated islets from Wistar rats and diabetic GotoKak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
0
38
1
Order By: Relevance
“…To clarify the link between reduced mitochondrial ATP production in the presence of substrates metabolizable in the Krebs cycle and reduced glucose oxidation by rapamycin, recovery of insulin release and ATP content in the presence of high glucose by ROS scavengers and activity of enzymes in the Krebs cycle were examined. Ouabain-induced endogenous ROS suppresses mitochondrial metabolism in the Krebs cycle, subsequently reducing ATP production, and reduces glucose-induced insulin release and ATP levels in the presence of high glucose, which is recovered by the suppression of endogenous ROS production and by ROS scavenge (Kajikawa et al 2002, Kominato et al 2008). High glucose raises ROS level in b-cells (Bindokas et al 2003, Sakai et al 2003, which is also found in our previous study (Kominato et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To clarify the link between reduced mitochondrial ATP production in the presence of substrates metabolizable in the Krebs cycle and reduced glucose oxidation by rapamycin, recovery of insulin release and ATP content in the presence of high glucose by ROS scavengers and activity of enzymes in the Krebs cycle were examined. Ouabain-induced endogenous ROS suppresses mitochondrial metabolism in the Krebs cycle, subsequently reducing ATP production, and reduces glucose-induced insulin release and ATP levels in the presence of high glucose, which is recovered by the suppression of endogenous ROS production and by ROS scavenge (Kajikawa et al 2002, Kominato et al 2008). High glucose raises ROS level in b-cells (Bindokas et al 2003, Sakai et al 2003, which is also found in our previous study (Kominato et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Ouabain-induced endogenous ROS suppresses mitochondrial metabolism in the Krebs cycle, subsequently reducing ATP production, and reduces glucose-induced insulin release and ATP levels in the presence of high glucose, which is recovered by the suppression of endogenous ROS production and by ROS scavenge (Kajikawa et al 2002, Kominato et al 2008). High glucose raises ROS level in b-cells (Bindokas et al 2003, Sakai et al 2003, which is also found in our previous study (Kominato et al 2008). However, our previous study shows that ROS scavenging does not affect glucose-induced insulin secretion from control islets, but increases that from GK-diabetic islets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence was determined using a spectrofluorophotometer (RF-5300PC; Shimazu, Kyoto, Japan) with excitation wavelength at 502 nm and emission wavelength at 523 nm. After 1 h incubation in the presence or absence of metformin, rotenone, ONOO − or hydrogen peroxide with or without RNS scavenger (5 mmol/l α-tocopherol plus 2.3 mmol/l ascorbate) [27], fluorescence was measured and presented as a ratio with respect to the value at time zero.…”
Section: Determination Of Reactive Nitrogen Species Onoomentioning
confidence: 99%
“…Because of their fundamental importance to cell homeostasis by governing signal-transduction processes, kinases -especially members of the Rous sarcoma virus oncogene protein kinases (Src) and protein kinase C (PKC) families -are commonly crucial in various pathologies. Intriguingly, homologous to the Src and/or PKC activation was found to govern multiple pathological processes in hyperglycemia [21][22][23] and lipotoxicity [24,25]. Because similar pathways were also described as leading to cellular differentiation [17], the actual physiological outcome might depend on the pattern of activated pathways rather than on a single phenomenon.…”
Section: The Dark Side Of Mitochondrial Protein Phosphorylationmentioning
confidence: 99%